Impact of Pandemic-Driven Parental Fear on Childhood Immunization Rates: Examining Attitudes Toward Vaccination During Crisis Periods in Türkiye - Erkin, Özüm; Göl, İlknur (UI Scholars Hub, 2025)
Background: This study aimed to investigate the effect of parents’ fear of coronavirus on their attitudes towards the vaccination of their children. Methods: The study was conducted with 2,350 parents who were selected by using the snowball sampling method. The questionnaire included a personal information form, the Public Attitude towards Vaccination Scale – Health Belief Model, and the Fear of COVID-19 Scale. Results: The scores of the study group from the sub-dimensions of the Public Attitude towards Vaccination Scale Health Belief Model were as follows: 17.39 ± 2.92 perceived susceptibility, 16.74 ± 3.19 perceived severity, 21.10 ± 3.54 perceived benefits, 14.16 ± 5.08 perceived barriers, and 22.07 ± 2.93 perceived health motivation. The score of the group on the total Fear of COVID-19 Scale was 21.58 ± 5.92. A statistically positive correlation was found between the scores obtained from the sub-dimensions and the Fear of COVID-19 Scale, except for the ‘perceived barriers’ sub-dimension. Conclusions: The study found that parents’ fear of COVID-19 positively influenced their attitudes toward childhood vaccination; however, more than three-quarters of parents reported delaying their children’s vaccinations due to concerns about COVID-19 exposure, highlighting the need for better parental education on vaccines and vaccine safety.